2011
DOI: 10.1111/j.1600-079x.2011.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA and gene expression analysis of melatonin-exposed human breast cancer cell lines indicating involvement of the anticancer effect

Abstract: MicroRNAs (miRNAs) are small, noncoding RNAs that play a crucial role in regulation of gene expression. Recent studies have shown that miRNAs implicated in initiation and progression of various human cancers, including breast cancer and also analysis of miRNA expression profiles in cancer provide new insights into potential mechanisms of carcinogenesis. Melatonin, N-acetyl-5-methoxytryptamine, is synthesized by the pineal gland in response to the dark/light cycle and has been known to act as a synchronizer of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(60 citation statements)
references
References 48 publications
1
59
0
Order By: Relevance
“…In hypoxic PC-3 prostate cancer cells, melatonin was shown to inhibit angiogenesis, an effect of importance to cancer growth that was concluded to be mediated by miR-3195 and miR-374b [39]. A more detailed study in MCF-7 breast cancer cells revealed alterations in the expression of 22 miRNAs by either 1 nM or 100 nM melatonin [40]. Twelve miRNAs were significantly upregulated and ten others downregulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hypoxic PC-3 prostate cancer cells, melatonin was shown to inhibit angiogenesis, an effect of importance to cancer growth that was concluded to be mediated by miR-3195 and miR-374b [39]. A more detailed study in MCF-7 breast cancer cells revealed alterations in the expression of 22 miRNAs by either 1 nM or 100 nM melatonin [40]. Twelve miRNAs were significantly upregulated and ten others downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve miRNAs were significantly upregulated and ten others downregulated. According to the analysis of their 5'-utr sequences, the 22 miRNAs should be capable of targeting the remarkable number of 2029 mRNAs [40].…”
Section: Discussionmentioning
confidence: 99%
“…In MCF-7 cells treated with 100 nM melatonin, 22 miRNAs were differentially expressed compared to controls; 12 of them were up-regulated and 10 down-regulated [171]. At the near-physiological concentration of 1 nM, four up-regulated and one down-regulated miRNAs were detected.…”
Section: Melatonin Cancer and Epigeneticsmentioning
confidence: 99%
“…[18][19][20][21] Previous studies have indicated that miRNAs play crucial roles in diverse physiological processes, including development, cell proliferation, differentiation, metabolism, migration and apoptosis. [22][23][24][25] Increasing evidence also suggested that miRNAs can regulate bone development and regeneration and are directly involved in the pathogenesis of numerous of orthopaedic conditions, such as intervertebral disc degeneration, osteoarthritis, osteoporosis and osteosarcoma. [26][27][28][29] Importantly, the roles of microRNAs in many of these orthopaedic conditions have been critically assessed.…”
Section: Introductionmentioning
confidence: 99%